DOES PRINCIPAL'S MINDSET HAVE CORRELATION WITH SCHOOL'S WORK CULTURE? - Kurniady, Dedy Achmad; Ma’mun, Muflih (EARR (Educational Administration Research and Review), 2018)
The success of school principals in changing the work culture of a better school depends on the mindset of change they have. This study seeks to prove whether or not there is an influence on the principal's mindset of leadership on work culture in schools. The research was conducted on 156 state Junior High School’s teachers in West Bandung Regency, West Java. Through survey methods and quantitative approaches, the data obtained were analyzed using correlation technique analysis.  The results showed that the principal's mindset had a significant correlation with school's work culture. This is based on Pearson's correlation value of 0.510, and included in the strong correlation category. As a recommendation, school principals must have a transformative, innovative and visionary principal’s mindset in building a work culture in schools.